2014
DOI: 10.1186/1471-230x-14-174
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transoral fundoplication for treatment of chronic gastroesophageal reflux disease incompletely controlled with high-dose proton-pump inhibitors therapy: a randomized, multicenter, open label, crossover study

Abstract: BackgroundThe aim of this randomized, crossover study was to determine if transoral fundoplication (TF) could further improve clinical outcomes in partial responders to high-dose (HD) proton-pump inhibitor (PPI) therapy and to evaluate durability of TF.MethodsIn seven United States centers, patients with hiatal hernia ≤2 cm and abnormal esophageal acid exposure (EAE) were randomized to TF (n = 40) or HD PPIs (n = 23) group. At 6-month follow-up, PPI patients underwent crossover. We assessed clinical outcomes 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 23 publications
3
67
0
Order By: Relevance
“…In fact, PPI therapy may be less effective in controlling abnormal EAE in certain patients than previously thought [15]. The rate of pH normalization off PPIs noted in our study 3 years post-TF (40 %) is comparable to rates of pH normalization reported in patients on double-dose PPI therapy (approximately 50 %) [20, 23].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In fact, PPI therapy may be less effective in controlling abnormal EAE in certain patients than previously thought [15]. The rate of pH normalization off PPIs noted in our study 3 years post-TF (40 %) is comparable to rates of pH normalization reported in patients on double-dose PPI therapy (approximately 50 %) [20, 23].…”
Section: Discussionsupporting
confidence: 59%
“…This is not the case in patients who receive the TF procedure, as de novo occurrence of post-procedure dysphagia and bloating is virtually nonexistent [14, 15, 24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique does not affect other future therapeutic options. Our results must be interpreted cautiously considering the limitations of this study, most notably the small sample of 8 patients only, the two centres, two gastroenterologists study; follow-up grossly observational; unique use of subjective measures of GERD severity by GERD-HRQL score (without follow up by endoscopy), relative short follow up duration (1 year) and restriction to sub-groups of GERD patients [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…TF may provide further control of acid reflux symptoms and heal esophagitis in patients who are refractory to high-dose PPI therapy. 16 A randomized, multicenter, open-label, crossover study evaluated whether TF could further improve clinical outcomes in partial PPI responders and the durability of such an effect. Patients with GERD and hiatal hernia ࣘ2 cm were randomized to the TF (n = 40) or high-dose PPI therapy (n = 23) groups.…”
Section: Available Technologies To Close the Gerd Treatment Gapmentioning
confidence: 99%